Leptoomidae, a new family of Eocene fossil Chalcidoidea (Hymenoptera), and family classification of Eocene fossil genera originally described in Neanastatinae (Eupelmidae) - Gibson, Gary A. P.; Fusu, Lucian (Zootaxa, 2023)
Leptoomidae Gibson fam. nov. (Chalcidoidea) is described for the Eocene Baltic amber fossil genera Leptoomus Gibson, type genus, reassigned from Tanaostigmatidae, and Neanaperiallus Gibson, reassigned from Neanastatinae (Chalcidoidea: Eupelmidae) sensu Gibson (2009). One new species of Neanaperiallus, N. defunctus Fusu sp. nov., is described. The new family is differentiated from other families of Chalcidoidea that are partly characterized by a greatly enlarged acropleuron. In species of Leptoomidae the prepectus is anteriorly rounded to angulate and extends to or slightly over the posterolateral margin of the pronotum, with the dorsal prepectal margin intersecting the base of the tegula distinctly anterior to and forming an almost right-angle with the posterior margin of prepectus, and the posterior margin truncate along the anterior margin of the acropleuron. This prepectal structure is similar to that in Tanaostigmatidae and Cynipencyrtidae, except the prepectus is elongated anteriorly exterior to the pronotum in Tanaostigmatidae and interior to the lateral surface of the pronotum in Cynipencyrtidae. A difference in prepectal structure also indicates that an anteriorly elongated mesoscutal process internal to the pronotum in Encyrtidae is convergent to that of Cynipencyrtidae, and similarity in shape of the prepectus among Encyrtidae, Eopelma Gibson and Neanastatus Girault might be functionally correlated with an anterior elongation of the mesoscutal process. New or corrected morphological data are provided for the two included genera. Of other Eocene fossil genera originally classified in Neanastatinae, Brevivulva Gibson and Propelma Trjapitzin, are assigned to Neanastatidae sensu Burks et al. (2022) based on similar mesoscutellar structures. Possible relationships of Aspidopleura Gibson, a taxon with a puzzling combination of features, are discussed. Because Aspidopleura cannot be placed with confidence in any extinct or extant higher taxon it is treated as incertae sedis at family level within Chalcidoidea.